Improving Learning Experience Through Augmented Reality Media Workshop Oriented on Local Wisdom at the Megalithic Site of Poso - Nadjamuddin, Lukman; Jamaludin, Jamaludin; Rore, Idrus; Zaky, Muhammad; Tadeko, Nurgan (CV. Rayyan Dwi Bharata, 2024)
This research addresses significant challenges in enhancing the quality and relevance of education in remote areas of Indonesia, particularly in Poso Regency, Central Sulawesi. The primary issues identified include low student engagement in learning activities related to local culture and history, as well as a lack of innovative teaching methods that effectively integrate local wisdom with modern educational technologies. This study explores the potential of Augmented Reality (AR) as a solution to these challenges by developing and implementing AR-based educational media focused on the Megalithic Sites in Poso. The research employed an action research approach, involving a purposive sample of teachers from Poso who participated in a specially designed AR training program. The program included sessions on the relevance of AR to the